2019
DOI: 10.3389/fpsyg.2019.01829
|View full text |Cite
|
Sign up to set email alerts
|

Character Strengths Lead to Satisfactory Educational Outcomes Through Strength Use: A Longitudinal Analysis

Abstract: Despite the flourishing of positive education, understanding of whether different character strengths have different predictive effects on academic achievement/well-being and the mechanisms of actions between character strengths are limited. Specifically, this study adopted strength use as a mediator to understand how character strength (assessed by caring, inquisitiveness, and self-control) is associated with students’ end-of-year academic achievements and eudaimonic well-being. Survey data from 349 adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 57 publications
3
15
0
Order By: Relevance
“…Changes in resilience factors (e.g., self-efficacy, positive thinking, altruism, and goal setting) could mediate enhanced personal resilience at the 3-month follow-up sessions (Yu et al, 2015). The awareness and application of character strengths may play such a mediating role (Bu & Duan, 2019; Duan et al, 2019; Tang et al, 2019). Fourth, WBT and character strength–based interventions exhibited the logic of CBT model and were successfully combined with CBT in previous studies.…”
Section: Discussion and Applications To Practicementioning
confidence: 99%
“…Changes in resilience factors (e.g., self-efficacy, positive thinking, altruism, and goal setting) could mediate enhanced personal resilience at the 3-month follow-up sessions (Yu et al, 2015). The awareness and application of character strengths may play such a mediating role (Bu & Duan, 2019; Duan et al, 2019; Tang et al, 2019). Fourth, WBT and character strength–based interventions exhibited the logic of CBT model and were successfully combined with CBT in previous studies.…”
Section: Discussion and Applications To Practicementioning
confidence: 99%
“…Fourth, the concurrent and predictive validity of the AES should be further enhanced using larger samples and various established measures. Finally, positive education emphasizes that academic achievement and well-being are equally important components of educational outcomes (Tang, Li, Duan, Mu, & Cheng, 2019). Future studies should examine the predictive effect of the AES on adolescents’ well-being as well as its underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fairness has shown a positive association with selfreported GPA [49]. Among high school students, the caring factor has been positively associated with final exam grades [50]. Regarding self-control, this factor and some of its strengths have been related to academic performance.…”
Section: Character Strengths As Predictive Factors Of Academic Engagement Career Self-doubt and Academic Performancementioning
confidence: 99%
“…Studies using self-control scales have demonstrated a positive association between this construct and academic achievement [51][52][53]. In addition, the self-control factor has also shown a positive association with final exam grades in high school students [50]. Among university students, self-regulation, perseverance and prudence [49], as well as honesty and humility, [48] have demonstrated positive associations with academic scores.…”
Section: Character Strengths As Predictive Factors Of Academic Engagement Career Self-doubt and Academic Performancementioning
confidence: 99%
See 1 more Smart Citation